Plant growth regulators priming enhances seed quality and enzymes activity in mungbean (Vigna radiata L.) - Tiwari, T.N.; Kamal, Dipti; Singh, R.K.; Prasad, S. Rajendra (Annals of Agricultural Research, 2016)
Field experiments were conducted at the research farm of Directorate of Seed Research, Mau toimprove the germination, stand establishment, and growth of mungbean employing the seed primingtechniques. Seeds of two mungbean varieties viz: Samrat and Pusa Vishal were sand primed with50 ppm and 100 ppm solution of growth regulators viz. Gibberellic Acid (GA3), Indol Acetic Acid(IAA), Indol butyric acid (IBA) and Kinetin separately for 8 hours. Experiments were conducted inlaboratory as well as in the cemented pots of 15 kg capacity. The results revealed that PGR primingshowed significant enhancement in the seed quality parameters, growth, nitrate assimilatoryenzymes and alpha amylase activity over unprimed control. Among treatments performance ofGA3 @ 100 ppm was superior over others in respect of seed germination, field emergence, seedlinggrowth, vigour index 1 & 2, nitrate assimilatory enzymes including nitrate reductase and nitritereductase and germination enzyme alpha amylase.